2021
DOI: 10.1371/journal.pone.0251446
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic predictive value of neutrophil-to-lymphocyte ratio in thyroid cancer adjusted for tumor size

Abstract: The role of systemic inflammation has not been clearly defined in thyroid cancers. There have been conflicting reports on whether systemic inflammatory markers have predictive value for thyroid cancers. We aimed to evaluate the association between systemic inflammatory markers and clinicopathological factors in thyroid cancers and to assess their predictive value for thyroid cancers in detail. Five hundred thirty-one patients who underwent surgery for thyroid nodules were included. The patient population consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 28 publications
2
19
0
1
Order By: Relevance
“…Overall, preoperative values for platelet indices (platelets count, MPV, PCT, PDW) ESR, neutrophil count, lymphocyte count, NLR and PLR were similar to the postoperative determinations in PTC patients (Table 7). However, when analyzing the PTC patients based on the pathological report findings (multifocality, capsular invasion, vascular invasion, extracapsular extension, lymph nodes metastasis, autoimmune thyroiditis, pT stage; data not shown) our data exhibit lower median ESR levels before thyroidectomy in patients with no capsular invasion (12 (10) vs. 14 (14) mm/h, p = 0.043), and no extracapsular extension, respectively (12 (13) vs. 14 (14) mm/h, p = 0.030). When it comes to platelet indices, we found lower mean PLT before surgery in PTC patients with vascular invasion (233.63 ± 62.06 vs. 262.13 ± 55.97 × 10 3 /mm 3 , p = 0.013).…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…Overall, preoperative values for platelet indices (platelets count, MPV, PCT, PDW) ESR, neutrophil count, lymphocyte count, NLR and PLR were similar to the postoperative determinations in PTC patients (Table 7). However, when analyzing the PTC patients based on the pathological report findings (multifocality, capsular invasion, vascular invasion, extracapsular extension, lymph nodes metastasis, autoimmune thyroiditis, pT stage; data not shown) our data exhibit lower median ESR levels before thyroidectomy in patients with no capsular invasion (12 (10) vs. 14 (14) mm/h, p = 0.043), and no extracapsular extension, respectively (12 (13) vs. 14 (14) mm/h, p = 0.030). When it comes to platelet indices, we found lower mean PLT before surgery in PTC patients with vascular invasion (233.63 ± 62.06 vs. 262.13 ± 55.97 × 10 3 /mm 3 , p = 0.013).…”
Section: Resultsmentioning
confidence: 71%
“…Seretis et al were the first to show that NLR may predict the presence of PTC [11]. Subsequent studies showed higher NLR in PTC patients [22,32] and association with tumor size [14,33], extrathyroidal extension [33], lymph node metastases [34] or cancer recurrence [13]. Furthermore, a recent meta-analysis published by Feng et al…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This view has received support from others in the field. 51 , 52 Multivariate analyses in this study identified NLR and PPR as independent risk factors for PTC, implicating PPR and NLR in the pathogenesis and progression of PTC. ROC curve analysis revealed that PDW had a certain degree of diagnostic value for PTC (AUC, 0.61; 95% CI, 0.575 ~ 0.645) but low specificity, in accordance with the findings of Yu et al 39 These findings indicate the limitations of single platelet indicators in the diagnosis of PTC.…”
Section: Discussionmentioning
confidence: 67%
“…On the other hand, significant positive correlations between NLR, PLR, SII and GH, and IGF-1 were noted in the NFPA group during our investigation. Taking into consideration conflicting data about the link between tumor size and inflammatory markers, we performed the analysis of the correlation between CBC-derived indices and adenoma MD in GH-secreting tumors and NFPAs, but no correlations were observed [57][58][59]. Moreover, we did not observe any significant differences in the calculated ratios in acromegaly patients concerning glucose metabolism disturbances, hypertension, coronary artery disease, obstructive sleep apnea, carpal tunnel syndrome, degenerative changes in bones and joints, and benign neoplasms.…”
Section: Discussionmentioning
confidence: 99%